Comparison of Palatal Rugae Pattern among Indian and Malaysian Population - Firoz Ismail; Rejeeh.E.P; Rajesh.H; Nabeel Abdul Vahid (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Tools for establishing identity is invaluable part of forensic sciences form the beginningof the profession. Odontology is one of such branches which in early days started in its crude form withidentification of different species and races within the species, currently is an individual subject withspecialist societies, journals and courses. Palatal rugae, was identified to be a potential tool for establishingidentity few centuries back itself but is not validated even today to be part of standard protocols. This is apilot study comparing two racial groups i.e., Indian and Malaysian with established parameters for palaterugae aiming at testing the feasibility of the parameters to be used in identification of individuals and racialgroups and also to provide preliminary data to make way to larger studies.Aims and Objectives: The aim of this pilot study is to explore the feasibility of palate prints as tool foridentification by, studying palate print in Indian and Malaysians and Comparison of plate Rugosity betweenIndians and Malaysians students for identification.Methodology: Study population was male Indian and Malaysian Medical and Dental students, age between18-25 years studying at Mangalore, India. Sample size 80 (40 in each group); were selected for studying ofPalatal Rugae. The palate impressions were collected using maxillary alginate cast. The parameters assessedwere: Total number of rugae, number of primary rugae (length- 5 to 10 mm), secondary rugae (3-5mm),fragmentary rugae (less than 3 mm). Comparison for two populations was done using non-parametric MannWhitney Test.Results: There were no statistically significant differences among the Indians and Malaysians in totalnumber and number secondary rugae in both sides more in Indians than Malaysians.There was statistically significant difference in number of the primary rugae and the fragmentary rugae,which in both sides were more in Indians than Malaysians.Conclusion: In conclusion, palatal rugae pattern are unique to an individual and their use in forensicidentification has been advocated and applied. Our study demonstrated significant difference in the numberof primary rugae on each side. It was more in Indians than Malaysians. This study demonstrated theuniqueness of rugae pattern in different individuals. Thus, it appears to be an effective & reliable source ofidentification.